Kryzys bankowy Ekwadoru w latach 1998-1999. Przyczyny, przebieg i metody wyjścia z kryzysu - Ostalecka, Agnieszka (Banking Crisis in Ecuador Between 1998 and 1999. The Causes, Development and Introduced Remedies, 2006)
The article presents the banking crisis, which took place in one of the Latin America countries, i.e. in Ecuador. As a starting point the article describes the macroeconomic and banking system situation before emerging of the banking crisis and the main causes of its outbreak. The second part of the article presents its development and measures, which were introduced in order to overcome the crisis situation. As a conclusion it presents the estimation prepared by the International Monetary Fund concerning the total cost of the banking crisis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 16-26